Pajak, Retribusi, dan PAD Sah: Trio Penggerak Pendapatan Kota Pekalongan - Vinko Satria Pekerti; Sarastanto Aulia Heru Pranoto; Zahron Zahron (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
Law Number 23 of 2014 grants broad authority to local governments to regulate and manage their own affairs, including regional financial management, with the main objective of increasing fiscal independence through the optimization of Local Own-Source Revenue (Pendapatan Asli Daerah or PAD). PAD, which is derived from regional taxes, regional levies (retributions), profits from regionally owned enterprises, and other legitimate local revenues, serves as an important indicator of regional independence. The purpose of this study is to determine the effect of Regional Taxes, Regional Retributions, and Other Legitimate Local Revenues on the Local Own-Source Revenue (PAD) of Pekalongan City. The data used in this study consist of both primary and secondary data. The population and sample in this study are the Local Revenue Realization Reports from 2015–2024. The research variables include Regional Taxes, Regional Retributions, Other Legitimate Local Revenues, and PAD. The data collection method uses descriptive analysis, while the data analysis method employs quantitative descriptive analysis using multiple linear regression. The results of the study indicate that Regional Taxes (X1) have a positive and significant effect on PAD, as shown by the t-test result where the t-value of 9.162 > 1.812 and a significance value of 0.000 < 0.05. Regional Retributions (X2) also have a positive and significant effect on PAD, indicated by the t-value of 8.821 > 1.812 and a significance value of 0.000 < 0.05. Other Legitimate Local Revenues (X3) similarly have a positive and significant effect on PAD, with a t-value of 9.482 > 1.812 and a significance value of 0.000 < 0.05. It is recommended that the Pekalongan City Government optimize existing tax sources through tax audits and enforcement, digitization of the Regional Tax Information System, tax base expansion by identifying new economic potentials, tax education and socialization, improvement of service quality, rationalization and adjustment of Regional Retribution tariffs, optimization of retribution collection systems through digitalization, enhancement of the performance of regionally owned enterprises (BUMD) to maximize dividend income, and optimization of asset and cash management.